DEVELOPMENT OF RESEARCH AND COMMUNITY SERVICE INFORMATION SYSTEM AT THE INSTITUTE FOR RESEARCH AND COMMUNITY SERVICE UNIVERSITY OF PALANGKA RAYA - Abertun Sagit Sahay; Felicia Sylviana; Rony Teguh; Devina Devina (Universitas Palangka Raya, 2018)
The Institute for Research and Community Service University of Palangkaraya (IRCSUPR) manages research activities, community services and controls the administration ofnecessary resources. Therefore, an application is requiredto record a lot of data from theproposal to the final report of research and community servicethat ultimately is expected tobe a control and evaluation on the performance of all parties involved.The methodology used in the development of this application there are several stagesranging from problem identification, needs analysis, design (which includes architecturedesign, database design, interface design and website navigation design), coding, testingand maintenance. On the testing stage used blackbox testing method.The results achieved from the making of this application there are 4 actors areadministrators, proposers, reviewers and operators who have different access rights inaccordance with its function. While from the results of the testing is known that all thefunctionality of the system is running well in accordance with the required and designedpreviously.